2020
DOI: 10.1021/acs.inorgchem.9b03412
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Solid-State Phase Transitions between Au–P Complexes Accompanied by Switchable Fluorescence

Abstract: Six complexes {(3-bdppmapy)(AuCl) 2 } n (1−6; 3-bdppmapy = N,N′-bis(diphenylphosphanylmethyl)-3-aminopyridine and tht = tetrahydrothiophene) were simultaneously formed by the reaction of Au(tht)Cl and 3-bdppmapy in CH 2 Cl 2 followed by infusion with hexane. Complexes 4−6 could be produced independently by volatilizing solvent in air, solidstate heating, or solvothermal reaction. The PPh 2 −Au−Cl moieties extended in different directions, forming Au−Au and Au−Au−Au interactions. Complex 4 could be converted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Slow evaporation from a 2:1 molar ratio of [AuCl­(tht)] and 3-bdppmapy [tht = tetrahydrothiophene, 3-bdppmapy = N , N ′-bis­(diphenylphosphanylmethyl)-3-aminopyridine] in CH 2 Cl 2 /hexane afforded [(AuCl) 2 (3-bdppmapy)]·CH 2 Cl 2 ·2H 2 O ( 156a ) . In the structure of 156a , determined by X-ray crystallography, a pair of [(AuCl) 2 (3-bdppmapy)] units are in close proximity with an intermolecular Au···Au separation of 3.2197(6) Å and one intramolecular Au···Au separation of 3.0687(6) Å.…”
Section: Vapochromic Effectsmentioning
confidence: 99%
“…Slow evaporation from a 2:1 molar ratio of [AuCl­(tht)] and 3-bdppmapy [tht = tetrahydrothiophene, 3-bdppmapy = N , N ′-bis­(diphenylphosphanylmethyl)-3-aminopyridine] in CH 2 Cl 2 /hexane afforded [(AuCl) 2 (3-bdppmapy)]·CH 2 Cl 2 ·2H 2 O ( 156a ) . In the structure of 156a , determined by X-ray crystallography, a pair of [(AuCl) 2 (3-bdppmapy)] units are in close proximity with an intermolecular Au···Au separation of 3.2197(6) Å and one intramolecular Au···Au separation of 3.0687(6) Å.…”
Section: Vapochromic Effectsmentioning
confidence: 99%
“…We [11][12][13][14][15][16]29], and others [17,[19][20][21][22], have previously used Mannich condensations as a versatile method for the synthesis of aminomethylphosphines. Accordingly, two equivalents of Ph 2 PCH 2 OH were reacted with one equivalent of the amine, for 24 h at r.t. under N 2 , yielding the desired phenol-substituted ditertiary phosphines 1a-e and 3 (Scheme 1).…”
Section: Ligand Synthesismentioning
confidence: 99%
“…For a number of years, we [11][12][13][14][15][16], and others [17][18][19][20][21][22], have been interested in aminomethylphosphines, readily amenable by Mannich condensation reactions. Such interest stems from the relative ease of accessing P-monodentate ligands based on a P-C-N linker [11,15,16,19,20,22] or P/P-bidentate derivatives bearing a P-C-N-C-P backbone [12][13][14][17][18][19]21]. Previously, we have shown that the N-arene group can be easily tuned with, for example, various H-bonding donor/acceptor sites based on -CO 2 H/OH groups [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the thermal-activated non-radiative decay, many other factors may be activated or influenced by temperature, including the effective molecular conformation or configuration transformation of flexible systems, 61,62 the degree of inter-or intramolecular π-π stacking and metal-metal interactions existing in aggregates or clusters of Rh(I), Pt(II), Cu(I), Ag(I), and Au(I) complexes, 39,[63][64][65] the dynamic association or dissociation process of metal and lanthanide complexes, 66,67 phase transition, [68][69][70][71] the degree of inter-or intramolecular energy transfer of donor/acceptor systems, 72,73 as well as the thermal equilibrium of different excited states. 74,75 These mechanisms will be discussed in more detail in specific examples in the following chapters.…”
Section: Zhong-liang Gongmentioning
confidence: 99%
“…However, the emission intensity changes could also be caused by many other factors, such as the dynamic association/dissociation process or phase transition. 66,71 The shift of λ emi is another general readout during the studies of thermo-responsive materials, which could be a result of dynamic thermal-equilibrium of different excited states or the change of the energy/electron transfer efficiency. 76,77 The shift of λ emi often leads to the emission color changes of materials, allowing us to conveniently monitor the thermo-responsive process.…”
Section: Zhong-liang Gongmentioning
confidence: 99%